Relation of serum phosphorus levels to the incidence of atrial fibrillation (from the Atherosclerosis Risk in Communities [ARIC] study) - Lopez, F.; Agarwal, S.; Grams, M.; Loehr, L.; Soliman, E.; Lutsey, P.; Chen, L.; Huxley, Rachel; Alonso, A. (2013)
High serum phosphorus levels have been linked with vascular calcification and greater cardiovascular morbidity and mortality. We assessed whether serum phosphorus was associated with the atrial fibrillation (AF) incidence in a large community-based cohort in the United States. Our analysis included 14,675 participants (25% black, 45% men) free of AF at baseline (1987 to 1989) and with measurements of fasting serum phosphorus from the Atherosclerosis Risk In Communities (ARIC) study. The incidence of AF was ascertained through the end of 2008 from study visit electrocardiograms, hospitalizations, and death certificates. Cox proportional hazard models were used to estimate the hazard ratios of AF by the serum phosphorus levels, adjusting for potential confounders. During a median follow-up of 19.7 years, we identified 1,656 incident AF cases. Greater serum phosphorus was associated with a greater AF risk: the hazard ratio of AF with a 1-mg/dl increase in serum phosphorus was 1.13 (95% confidence interval 1.02 to 1.26). No significant interaction was seen by race (p = 0.88) or gender (p = 0.51). The risk of AF was increased in association with greater serum phosphorus in those with an estimated glomerular filtration rate of =90 ml/min/1.72 m2 but not among those with an estimated glomerular filtration rate of <90 ml/min/1.72 m2. The total corrected calcium levels were not related to AF risk; however, greater levels of the calcium-phosphorus product were associated with greater AF risk. In conclusion, in the present large population-based study, greater levels of serum phosphorus and the related calcium-phosphorus product were associated with a greater incidence of AF. © 2013 Elsevier Inc. All rights reserved.